Natural history notes. Dasia vittata (Bornean Striped Tree Skink) Predation. - Pang, Sing Tyan; Elvia Chong, Qi Ern; Indraneil, Das (Society for the Study of Amphibians and Reptiles, 2024)
The article documents predation by the skink, Dasia vittata by Hemidactylus frenatus.